Postsynaptic Signaling via the μ-Opioid Receptor: Responses of Dorsal Horn Neurons to Exogenous Opioids and Noxious Stimulation - Trafton, Jodie A. (J Neurosci, 2000)
Although both pre- and postsynaptic mechanisms have been implicated in the analgesia produced by μ-opioids at the spinal cord, it is not known under what conditions these different controls come into play. Because the μ-opioid receptor (MOR) can be visualized in individual lamina II excitatory interneurons and internalizes into endosomes on ligand binding, we tested whether MOR internalization could be monitored and used to measure postsynaptic MOR signaling. To test whether endogenous opioids modulate these lamina II interneurons during noxious stimulation, we next assessed the magnitude of postsynaptic MOR internalization under a variety of nociceptive conditions. As observed in other systems, we show that MOR internalization in dorsal horn interneurons is demonstrated readily in response to opioid ligands. The MOR internalization is dose-dependent, with a similar dose–response to that observed for opioid-induced increases in potassium conductance. We demonstrate that MOR internalization in lamina II neurons correlates precisely with the extent of analgesia produced by intrathecal DAMGO. These results suggest that MOR internalization provides a good marker of MOR signaling in the spinal cord and that postsynaptic MORs on lamina II interneurons likely participate in the analgesia that is produced by exogenous opioids. We found, however, that noxious stimuli, under normal or inflammatory conditions, did not induce MOR internalization. Thus, endogenous enkephalins and endomorphins, thought to be released during noxious peripheral stimuli, do not modulate nociceptive messages via postsynaptic MORs on lamina II interneurons. We suggest that any endogenous opioids that are released by noxious stimuli target presynaptic MORs or δ-opioid receptors.